2009
DOI: 10.1089/ars.2009.2601
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen Peroxide in NF-κB Activation: From Inducer to Modulator

Abstract: Hydrogen peroxide (H2O2) has been implicated in the regulation of the transcription factor NF-kappaB, a key regulator of the inflammatory process and adaptive immunity. However, no consensus exists regarding the regulatory role played by H2O2. We discuss how the experimental methodologies used to expose cells to H2O2 produce inconsistent results that are difficult to compare, and how the steady-state titration with H2O2 emerges as an adequate tool to overcome these problems. The redox targets of H2O2 in the NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
181
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(192 citation statements)
references
References 128 publications
6
181
1
2
Order By: Relevance
“…To corroborate these findings, MEFs were exposed to glucose oxidase as an exogenous source of oxidative stress (22). Similar to the pattern of survival following serum starvation, WT MEFs demonstrated a time-and dose-dependent increase in cell death after glucose oxidase exposure (Fig.…”
Section: Akbi Mefs Are Resistant To Oxidative Stress-induced Cellsupporting
confidence: 53%
“…To corroborate these findings, MEFs were exposed to glucose oxidase as an exogenous source of oxidative stress (22). Similar to the pattern of survival following serum starvation, WT MEFs demonstrated a time-and dose-dependent increase in cell death after glucose oxidase exposure (Fig.…”
Section: Akbi Mefs Are Resistant To Oxidative Stress-induced Cellsupporting
confidence: 53%
“…They have in common that they are not receptor kinases by themselves, but work through associated kinases, as, for example, described for recruitment of the IL-1R-associated kinase (IRAK) in IL-1 signaling (312). In some cell types the genuine system receptors may be by-passed by H 2 O 2 (358).…”
Section: Basics Of Nf-kb Activationmentioning
confidence: 99%
“…Conflicting observations were also made with H 2 O 2 itself. A critical review analyzing 40 articles on NF-jB activation by H 2 O 2 alone or in conjunction with suitable cytokines revealed that H 2 O 2 did not consistently lead to NF-jB activation: an activation of NFjB was observed just in one third of the investigations, whereas in one-third H 2 O 2 inhibited NF-jB activation and had no effect whatsoever in another third (358). This puzzling scenario is hard to explain.…”
Section: Redox Regulation Of Nf-kb Activationmentioning
confidence: 99%
See 2 more Smart Citations